Spatial Variability of Soil Texture as a Determinant of the Erodibility Variable at Gullies in Eastern Nigeria - Igwe, P. U.; Ajadike, J. C.; Ogbu, S. O. (Journal of Sustainability and Environmental Management, 2024)
The soil texture (%sand, %silt and %clay) variable is a determinant of the erodibility variable linked to the severity of gully erosion. In Eastern Nigeria, a region in Nigeria where gully erosion predominates, the two variables have been studied in a segmented manner focusing only on localities, states and river basins, without a coverage of the area and the two concepts. Therefore, this study investigated the variability of soil texture as a determinant of the erodibility variable in Eastern Nigeria. The purposive sampling technique was used in selecting the nine most gully erosion-risk areas, one in each of the nine constituent states of the region. Then, one gully bearing the same name with the community where it is located was conveniently sampled from each of the most nine gullied areas, making a total of nine gullies. Physical observation, satellite imagery and experimental methods were used in collecting data from primary sources. A total of eighty-one (81) soil samples were collected, nine from each of the gullies at depths of 0-30cm, 30-60cm and 60-90cm for laboratory tests and analyses to determine %sand, %silt and %clay with which the erodibility variable was quantified. Results indicated that all of mean percentage sand, silt and clay as well as mean erodibility varied across the gullies. Nonetheless, %sand, %clay and erodibility varied significantly (p = 0.00 < 0.05) across the gullies: R = 0.843, R2 = 0.710; R = 844, R2 = 713; R = 0.908, R2 = 0.824 respectively, as %silt did not. The implication is that it is the sand and clay fractions, found to be high and low respectively that really and significantly determined the degree of the erodibility variable, gully erosion intensities plus problems. The study recommended avoidance of tillage during the rains, use of mulching and compost manure, use of plant charcoal, among others for improving the quality of soil texture as a panacea for lowering the erodibility variable and invariably gully erosion incidences in Eastern Nigeria.